Hernández Borge, Julio (2013). Galicia, unha poboación avellentada - Moreno Muñoz, Daniel (Documents d’Anàlisi Geogràfica, 2016)
Hernández Borge, Julio (2013) Galicia, unha poboación avellentada Santiago de Compostela: Universidad de Santiago de Compostela, 215 p. ISBN 978-84-15876-02-1